ANALISIS KECUKUPAN PANAS PADA PROSES PASTEURISASI DAGING RAJUNGAN (Portunus pelagicus) - Nur Aeni; Nurhidajah - (Jurnal Pangan dan Gizi, 2012)
Swimming crabs (Portunus pelagicus) is a fishery commodity that has high economic value in excess of a fairly high protein content and is composed of amino acids patterned approach needs amino acids in the human body The process of pasteurization is one way to maintain quality and prevent decayon crab meat. Object of research is crab meat (Portunus pelagicus). Research conducted a completely randomized study design (CRD) of one factors with the treatment combination of temperature and time of pasteurization as much as 12 levels. Dependent variable is the total number of microbes, whereas thecombination of pasteurization temperature and time as independent variables. Each experiment performed a total of three replications, in order to obtain 36 units of the experiment.The results showed that microbial heat resistance value of D 80 C, D 85 o C, 90 o C D and z values crab meat are 5.16; 3.67; 3.32 minutes and 52.63 o C. Heat resistance (P value) with sterile 5D level of 30.37 minutes. The combination of temperature and time of pasteurization with a P value of 30.37 minutes of pasteurization temperature of 80 C for 37.80 minutes, temperature 85 C for 30.37 minutes, the temperature of 90 C for 24.40 minutes. In the organoleptic properties of color, aroma, flavor and texture, heating at 80, 85, 90 oC for 5, 10, 15 minutes down a score of 7.0 (before pasteurization) to 5.0 to 7.0 (after pasteurization). The combination of temperature and time of pasteurization appropriate conclusions can be applied to crab meat processing industry. Need for additional research about the combination oftemperature and time of pasteurization and the effect on the subjective and objective quality as well as further research about the value of D of microbial pathogens in crab meat. Key words: microbial heat resistance, heat pasteurization adequacy, pasteurization, crab meat